Phytochemical screening and antioxidant activity of green tea (Camellia sinensis) infusions commercialized in portugal - Silva, Inês (2022)
Natural antioxidant products, like green tea (Camellia sinensis) have gained popularity worldwide and new products claiming antioxidant activity are frequent in the dietary supplement industry. However, information regarding the antioxidant properties of these products, in the labels, is usually scarce. In addition, the antioxidant properties of commercial teas were not investigated in detail. Therefore, the present study aims to investigate the phytochemical and antioxidant activity of C. sinensis infusions.